2022
DOI: 10.1021/acsomega.2c03968
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light-Mediated Photoactivated Sulfur Quantum Dots as Heightened Antibacterial Agents

Abstract: The need for antimicrobial or antibacterial fabric has increased exponentially in recent past years, especially after the outbreak of the SARS-CoV-2 pandemic. Several studies have been conducted, and the primary focus is the development of simple, automated, performance efficient and cost-efficient fabric for disposable and frequent-use items such as personal protective materials. In this regard, we have explored the light-driven antibacterial activity of water-soluble Sdots for the first time. Sdots are a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…We conducted a preliminary study of the antibacterial mechanism of iodine-doped implants. Numerous previous studies have shown that intracellular ROS production is a key mechanism for the effective killing of invading bacteria. , In this study, the fluorescence intensity of DCF was used to respond to the intracellular ROS level of bacteria. As shown in Figure A, significant green fluorescence signal was observed in the 3D-Ti–I group compared with the control group.…”
Section: Resultsmentioning
confidence: 99%
“…We conducted a preliminary study of the antibacterial mechanism of iodine-doped implants. Numerous previous studies have shown that intracellular ROS production is a key mechanism for the effective killing of invading bacteria. , In this study, the fluorescence intensity of DCF was used to respond to the intracellular ROS level of bacteria. As shown in Figure A, significant green fluorescence signal was observed in the 3D-Ti–I group compared with the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Preparation of ZnO NPs as nanofluids was done using two dispersants: (a) Polyethylene glycol (PEG), and (b) polyvinylpyrolidone (PVP). The antimicrobial effects of the NPs rise as their size decreases [89,90]. This is due to the damage caused by the NPs when they come into contact with the cell membrane, which results in the generation of reactive oxygen species (ROS) [19].…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…This method has a different mechanism than traditional antibiotics, which enables antibiotic resistance could be controlled in a new way . It is well-known that PDT processes advantages such as fewer side effects and localized treatment . However, the solubility of photosensitizers is poor, and it is difficult to achieve effective drug concentrations …”
Section: Introductionmentioning
confidence: 99%